AN INVESTIGATION ABOUT TEACHERS’ AND PARENTS’ ECO-FRIENDLY PRACTICES WITH PRE-SCHOOL CHILDREN (Third Sector Social Economic Review, 2017)
This study has been conducted for the purpose of determining how much teachers and parents of pre-school children taught them about recycling. The sample group of the study consists of 102 kindergarden teachers and 99 parents who were selected randomly from the kindergardens chosen by group sampling method in three municipality centres (Meram, Selçuklu ve Karatay) in Konya city in 2014. The study relied on general research method. Research data were collected by questionnaire method. Two scales have been used in the study for the stated purpose. First, “Teachers’ Application of Eco-friendly Activities for Kindergarden Students” which was developed by Buhan (2006) which he applied on kindergarden teachers. Second,“Parents’ Application of Eco-friendly Practices for their Children” which has been developed by Ersoy-Quadir and Temiz which has been applied on our sample kindergarden teachers. In addition, for the purpose of determining teachers’ and parents’ habits about recycling and eco-friendly purchasing, we applied the “Recycle Habits Scale” and “Eco-Friendly Purchasing Habits Scale” which were developed by Ersoy-Quadir (2014).In the study, we analyzed the relation among the sample group’s  number of variables and the factor categories by ""Pearson Correlation Coefficient."" According to the data, we found that most of the teachers taught eco-friendly practices to their students (% 73.5). Generally even higher percentage of parents taught eco-friendly practices to their children (% 81.8).
Keywords: Recycling; eco-friendly practices; pre-school children